Protein kinase C delta null mice exhibit structural alterations in articular surface, intra-articular and subchondral compartments - Yang, X.; Teguh, D.; Wu, Ping; He, B.; Kirk, T.; Qin, S.; Li, S.; Chen, H.; Xue, W.; Ng, B.; Chim, S.; Tickner, J.; et al. (BioMed Central Ltd., 2015)
© 2015 Yang et al. Introduction: Structural alterations in intra-articular and subchondral compartments are hallmarks of osteoarthritis, a degenerative disease that causes pain and disability in the aging population. Protein kinase C delta (PKC-d) plays versatile functions in cell growth and differentiation, but its role in the articular cartilage and subchondral bone is not known. Methods: Histological analysis including alcian blue, safranin O staining and fluorochrome labeling were used to reveal structural alterations at the articular cartilage surface and bone-cartilage interface in PKC-d knockout (KO) mice. The morphology and organization of chondrocytes were studied using confocal microscopy. Glycosaminoglycan content was studied by micromass culture of chondrocytes of PKC-d KO mice. Results: We uncovered atypical structural demarcation between articular cartilage and subchondral bone of PKC-d KO mice. Histology analyses revealed a thickening of the articular cartilage and calcified bone-cartilage interface, and decreased safranin O staining accompanied by an increase in the number of hypertrophic chondrocytes in the articular cartilage of PKC-d KO mice. Interestingly, loss of demarcation between articular cartilage and bone was concomitant with irregular chondrocyte morphology and arrangement. Consistently, in vivo calcein labeling assay showed an increased intensity of calcein labeling in the interface of the growth plate and metaphysis in PKC-d KO mice. Furthermore, in vitro culture of chondrocyte micromass showed a decreased alcian blue staining of chondrocyte micromass in the PKC-d KO mice, indicative of a reduced level of glycosaminoglycan production. Conclusions: Our data imply a role for PKC-d in the osteochondral plasticity of the interface between articular cartilage and the osteochondral junction.